VENEZUELAN EQUINE ENCEPHALOMYELITIS VIRUS VECTOR FOR THE RECOMBINANT EXPRESSION OF PROTEINS IN MAMMALIAN CELLS - Baltabekova , A.Zh.; Shagyrova , Zh.S.; Kim , Y.G.; Voikov , M.S.; Zhiyenbay , E.; Shustov , A.V. (Eurasian Journal of Applied Biotechnology, 2016)
Venezuelan equine encephalomyelitis virus (VEE) is a well-studied member of the genus Alphavirus in the family Togaviridae. The VEE virus is a popular vector for gene delivery in cell culture as well as for heterologous expression of recombinant proteins in cultures of vertebrate and insect cells. All VEE RNA synthesis occurs in the cytoplasm and during the course of recombinant protein expression from a gene cloned into the VEE genome, a number of molecular processes are excluded, which may otherwise represent a bottleneck in the expression system. Complementary DNA (cDNA) representing the full-length VEE genome was assembled and cloned into an Escherichia coli plasmid under the control of the SP6 RNA polymerase promoter. The gene encoding GFP was engineered into the VEE genome under the control of a synthetic copy of a viral 26S subgenomic RNA promoter. The RNA transcript of the recombinant virus was transfected into BHK-21 cells and by 36 h post-transfection, almost all cells in the culture exhibited bright GFP fluorescence. Titres of the virus produced in the transfected culture were measured for 5 days and found to be 8.4*105 TCID50 24 h post-transfection and 2.9*108 TCID50 by 3 days post-transfection. This article illustrates the basic steps of constructing a VEE-based vector and furthermore, demonstrates the rescue of the recombinant VEE variant engineered to produce model recombinant protein GFP. The VEE vector may be applicable in biopharmaceutical production in Kazakhstan.